Ficolin-2 Lectin Complement Pathway Mediates Capsule-Specific Innate Immunity Against Invasive Pneumococcal Disease - Nahm, Moon H.; Yu, Jigui; Calix, Juan J.; Ganaie, Feroze (Frontiers in Immunology, 2022)
Reports conflict regarding which lectin-microbial ligand interactions elicit a protective response from the lectin pathway (LP) of complement. Using fluorescent microscopy, we demonstrate the human lectin ficolin-2 binds to Streptococcus pneumoniae serotype 11A capsule polysaccharide dependent on the O-acetyltransferase gene wcjE. This triggers complement deposition and promotes opsonophagocytosis of encapsulated pneumococci. Even partial loss of ficolin-2 ligand expression through wcjE mutation abrogated bacterial killing. Ficolin-2 did not interact with any pneumococcal non-capsule structures, including teichoic acid. We describe multiple 11A clonal derivatives expressing varying degrees of wcjE-dependent epitopes co-isolated from single blood specimens, likely representing microevolutionary shifts towards wcjE-deficient populations during invasive pneumococcal disease (IPD). We find epidemiological evidence of wcjE impairing pneumococcal invasiveness, supporting that the LP’s ficolin-2 axis provides innate, serotype-specific serological protection against IPD. The fact that the LP is triggered by only a few discrete carbohydrate ligands emphasizes the need to reevaluate its impact in a glycopolymer-specific manner.